IMPLEMENTASI STRATEGI PEMBELAJARAN MUFRODAT DALAM MENINGKATKAN KEMAMPUAN BERBICARA BAHASA ARAB PADA ANAK MADRASAH DINIYAH AWALIYAH (MDA) DI DESA TANJUNG BARINGIN SIMARULAK - Nur Halimah Harahap; Mira Yanti Lubis; Aisyah Nasution; Nikmah Syahbani Nasution; Lenni Sari Lubis; Rafika Hasibuan; Nur Liana Hasibuan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Arabic is a compulsory subject at all Madrasah Diniyah Awaliyah (MDA) schools and is an essential part of the educational institution's curriculum. However, an oddity was found: most students found the teaching and learning process in class difficult and boring. In this case, the researcher conducted an Arabic language learning experiment using the mufrodat method on 23 local MDA students whose additional classes were held at the Al-Qur'an Education Park (TPQ) in Tanjung Baringin Simarulak village, with the aim of improving the students' speaking skills and incrasing the motivasion and interest of student’s learning at the MDA. This study employed a qualitative approach. This approach was chosen because the process of data collection was carried out through observation, interviews, and documentation. The interviews involved several elements such as teachers and students, while observations were conducted by listening to complaints experienced by students in the environment and observing the surrounding environment, which was characterized by the lack of Arabic language learning facilities. This led to a lack of interest in learning Arabic. Meanwhile, documentation consisted of photos of activities and student summary data. All of this data was carefully collected and analyzed. During the program, researchers found that the Mufrodat method was able to create a high level of enthusiasm among students and also stimulated a strong curiosity about Arabic, resulting in improved pronunciation.